An incomplete double movement: Spain's legislative strategy for platform courier reclassification. - Vieira, Tiago (International Labour Review, 2025)
This article analyzes Spain’s legislative efforts, particularly the 2021 Ley Rider, to reclassify platform-based food-delivery couriers as employees under conventional employment law. Drawing on an 18-month qualitative case study involving interviews, ethnographic observation, and document analysis, it finds that while couriers gained formal employment rights such as fixed salaries, paid leave, and social protections, challenges persist due to outsourcing practices, involuntary part-time work, and intensified algorithmic management. The latter, characterized by pervasive surveillance and micromanagement, undermines workers’ autonomy, trust, and fair treatment, with limited effectiveness of legal provisions granting unions access to platform algorithms. The study concludes that Spain’s regulatory approach represents an incomplete “double movement” toward re-embedding platform workers in traditional employment relations, highlighting the need for stronger legal frameworks and capacity-building to address algorithmic management’s impact on labor conditions.